UNBOXING UNDERSTANDING: SELF-EXPLANATION PROMPTING AS A KEY TO UNLOCKING DEEP LEARNING IN CALCULUS - Sufyani Marethi; Hadi Firdos Prabawanto (The American Journal of Social Science and Education Innovations, 2024)
Deep learning in calculus often poses challenges for students, requiring a nuanced approach to foster comprehension. This study explores the efficacy of self-explanation prompting as a key strategy for enhancing deep learning in calculus. The research investigates the impact of guided self-explanation prompts on students' understanding and retention of calculus concepts. By employing a carefully designed intervention, we aim to uncover the mechanisms through which self-explanation facilitates meaningful learning in calculus. The results highlight the potential of self-explanation as a powerful tool in the educational toolkit, shedding light on how it can unlock a deeper understanding of calculus concepts and improve overall learning outcomes.